(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Although prison life is widely studied, the experiences of women in Philippine provincial facilities remain under-researched. This qualitative case study explored the lived experiences of 11 pre-trial female detainees in two provincial jails in Samar to identify gender-specific challenges within the correctional system. Semi-structured interviews were analyzed thematically, revealing five primary themes: life before incarceration, emotional responses, prisoners’ needs, challenges in prison life, and coping mechanisms. Results indicate that while detainees demonstrate resilience and solidarity, they endure significant hardships, including prolonged legal delays, family separation, and inadequate institutional support. Grounded in Maslow’s hierarchy of needs and Rogers’ humanistic theory, the analysis demonstrates how unmet psychological and physical needs undermine inmate dignity. The study concludes that the intersection of gender and justice in provincial contexts necessitates urgent gender-responsive policies. Significant recommendations include improving access to mental health services, livelihood programs, and family support systems to facilitate successful rehabilitation and reintegration.